Efeito da desinfecção de canais protéticos na resistência adesiva de pinos de fibra de vidro à dentina radicular - Ravanello, Luciane Noal (2011)
The root canal preparation for placement of endodontical posts, more than in coronary preparations, produces smear layer rich in remains of dentine, filling materials and microorganisms, which may decrease the penetration and action of the adhesives, as well it favors the infection recidivation. This study investigated the effect of root canal disinfection on bond strength of glass fiber posts (White Post DC) cemented with two adhesive cements at cervical, middle and apical root. Sixty roots were randomly divided into six groups (n = 10) in accordance with the cleaning technique: water (control), 5% sodium hypochlorite and sodium hypochlorite 5% + ultrasonic agitation; and the strategies of cementation: etching with phosphoric acid 37% (Condac, FGM) +_Adper Single Bond 2 adhesive resin + RelyX ARC adhesive resin cement conventional or self-adhesive resin cementRelyX U100 (3M ESPE). After fiber posts cementation and core build-up with composite resin Z350 (3M ESPE), the reconstructed teeth were subjected to 1,000,000 cycles of mechanical fatigue (ER 11000, manufacturer, city, state, country). The specimens were then sectioned into slices of 2.0 mm thickness with a cutting machine (Labcut 1010, Extec, city, state, country) for the push-out test (EMIC City, PR, Brazil). The results were analyzed statistically (three-way ANOVA and Tukey´s test). Cleaning methods did not interfere on the bond strength in the groups with conventional cement and there was no difference between the thirds in the control groups and sodium hypochlorite, but in groups that used sodium hypochlorite associated with ultrasonic agitation, the cervical third provided significantly higher bond strength. In groups associated with the self-adhesive cement the bond strength was higher in the control group in all thirds; in the sodium hypochlorite group, the bond strength was greater in the apical third. However, there was no significant difference between the thirds in the control groups and sodium hypochlorite associated with ultrasonic agitation. The selfadhesive cement has provided higher bond strength than the conventional in all groups. In this study, the use of sodium hypochlorite reduced the bond strength for the self-adhesive cement.